Field experiments in economics - Harrison, Glenn W.; Carpenter, Jeffrey P.; List, John A., 1968- (Research in experimental economics, 2005)
Experimental economists are leaving the reservation. They are recruiting subjects in the field rather than in the classroom, using field goods rather than induced valuations, and using field context rather than abstract terminology in instructions. This volume examines the methodology of field experiments, and offers a wide array of applications of field experiments. The methodological issues revolve around the ability of field experimenters to ensure the same degree of control that lab experimenters claim. The applications cover issues such as risk and time preferences of the Danish population, savings decisions of the Canadian working poor, differences between the social preferences of American students and workers, the effect of educational vouchers on American school children, and differences in bargaining behavior across nations. This volume serves as an introduction to the issues and applications of this new area of experimental economics.